2015
DOI: 10.1097/bpo.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Osteoarticular Infection Update

Abstract: Musculoskeletal infections are a common cause of morbidity in children. A multitude of studies over the past few years have improved our knowledge and understanding of the etiology, diagnosis, and treatment of pediatric osteomyelitis and septic arthritis. Staphylococcus aureus continues to be the most common pathogen; however, new and innovative organism identification techniques are improving the speed and accuracy of diagnosis and increasing the identification of other less common organisms. Improved capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
0
29
1
Order By: Relevance
“…The high concurrency of osteomyelitis observed in this series is not surprising [5]. Several studies have shown a low bacterial recovery rate around 33-37% [1,2,6], which are much lower than that found in our study where the cultures resulted in a high return rate (70%). S. aureus was the most frequent bacterial agent isolated in our series.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The high concurrency of osteomyelitis observed in this series is not surprising [5]. Several studies have shown a low bacterial recovery rate around 33-37% [1,2,6], which are much lower than that found in our study where the cultures resulted in a high return rate (70%). S. aureus was the most frequent bacterial agent isolated in our series.…”
Section: Discussioncontrasting
confidence: 55%
“…Rapid recognition is necessary to initiate the appropriate treatment in a timely manner. Empiric antibiotic treatment is based on the patient's age and most likely organism involved in a given community [2].…”
mentioning
confidence: 99%
“…Finally, Candida spp. is another pathogen that may be identified from some cases of acute osteomyelitis (mainly spondylodiscitis) which requires a prolonged antifungal treatment and surgical debridement [ 44 ].…”
Section: Controversies In Managementmentioning
confidence: 99%
“…Author wants to emphasize that beta-lactam antibiotics should be used as an empirical therapy over clindamycin because an often use of clindamycin may develop resistance in MRSA, so it may not be helpful drug for future. Also K. kingae is recently found as one of the commonest emerging microbe in bone and joint infection 8 and betalactam antibiotics are better drugs to cover Kingella than clindamycin.…”
Section: Discussionmentioning
confidence: 99%